CONFORMITY AND INDIVIDUALISM IN EASTERN AND WESTERN SOCITIES: A COMPARATIVE LITERARY ANALYSIS OF “O`TKAN KUNLAR” (BYGONE DAYS) AND “THE MOON AND SIXPENSE” - Alimardonova Gulsevar Sirojiddinovna (Western European Studies, 2025)
This article demonstrates a comparative literary analysis of the conceptualizations of conformity and individualism in Eastern and Western civilizations through the writings “O`tkan kunlar” (Bygone Days) by Abdulla Qodiriy and Somerset Maugham`s “The Mooon and Sixpence”. Using traditional sociology and literary hermeneutics, the research investigates how each authors constructs social standards, personal freedom, and the tension between communal anticipations and individual ambitions. This study reveals cultural difference through a close reading of two 20th century novels Abdulla Qodiriy`s “O`tkan kunlar” (1926), a cornerstone of modern Uzbek literature, and “The Moon and Sixpence” (1919) by Somerset Maugham, a classic of British modernism
Keywords: conformism; individualism; cross-cultural literary analysis; society and the self